2017
DOI: 10.1002/cpt.787
|View full text |Cite
|
Sign up to set email alerts
|

Practical Recommendations for Therapeutic Drug Monitoring of Kinase Inhibitors in Oncology

Abstract: Despite the fact that pharmacokinetic exposure of kinase inhibitors (KIs) is highly variable and clear relationships exist between exposure and treatment outcomes, fixed dosing is still standard practice. This review aims to summarize the available clinical pharmacokinetic and pharmacodynamic data into practical guidelines for individualized dosing of KIs through therapeutic drug monitoring (TDM). Additionally, we provide an overview of prospective TDM trials and discuss the future steps needed for further imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
302
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(321 citation statements)
references
References 80 publications
10
302
2
7
Order By: Relevance
“…Additionally, TDM has been shown to improve safety and efficacy of many targeted oral anticancer drugs. 13,14 A relationship between plasma exposure and treatment outcome has been retrospectively established for imatinib in patients with GIST, 10 supporting the rationale for the use of TDM in GIST patients treated with imatinib. While the effect of TDM to redistribute patients to adequate plasma concentrations has been proven, it is currently unknown what the financial consequences of TDM is compared with fixed dosing.…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, TDM has been shown to improve safety and efficacy of many targeted oral anticancer drugs. 13,14 A relationship between plasma exposure and treatment outcome has been retrospectively established for imatinib in patients with GIST, 10 supporting the rationale for the use of TDM in GIST patients treated with imatinib. While the effect of TDM to redistribute patients to adequate plasma concentrations has been proven, it is currently unknown what the financial consequences of TDM is compared with fixed dosing.…”
Section: Introductionmentioning
confidence: 90%
“…A pooled population PK analysis of the steady‐state exposure‐response relationship for axitinib in a cohort of 168 renal cell carcinoma patients demonstrated that an axitinib AUC SS of >300 ng/mL/hr was associated with superior progression‐free survival of 13.8 vs 7.4 months (hazard ratio, 0.558 [95%CI, 0.379‐0.823]) and overall survival of 37.4 vs 15.8 months (hazard ratio, 0.489 [95%CI, 0.324‐0.738]) ( P < .001) . This result has not translated into a robust “threshold” C trough for axitinib to facilitate standard therapeutic drug monitoring–guided precision dosing for this drug . Similarly, the relationship between axitinib exposure and tolerability remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The TDM of anticancer drugs is becoming an important tool in treatment of patients with cancer, especially with increased use of oral anticancer drugs with highly variable bioavailability (B. Gao et al, ; Herbrink et al, ; Lankheet et al, ; Paci et al, ; Widmer et al, ; Yu et al, ). TDM has been shown to be a valuable intervention to optimize dosing of some anticancer drugs (Groenland et al, ; Paci et al, ; Verheijen et al, ; Widmer et al, ; Yu et al, ); however, prospective research is needed to further confirm these TDM targets. With the growing class of oral anticancer therapies, there is an increasing demand for TDM for which new assays have to be developed and validated.…”
Section: Future Perspectivesmentioning
confidence: 99%